2011
DOI: 10.1007/bf03262785
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser irradiation and fluoride uptake in human teeth

Abstract: There is an enhanced capability of lasers to increase fluoride uptake of enamel and providing protection to enamel surface from acid attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…As described above, this method enhances the absorption of the laser beam on the tissue surface, changing its chemical and morphological structure, and increasing its acid resistance (10,11,22,23). Previous studies revealed that diode laser increases fluoride uptake when enamel is irradiated in the presence of a fluoride compound, and they also stated that enamel must be irradiated in the presence of a pigmented coating substance to increase the acid resistance of enamel (10,11). According to this, the pigmented 5% NaF varnish used here acted as a photo-absorber for the diode laser photons, generating photothermal effects in enamel and changing the morphology of the enamel and, therefore, its roughness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, this method enhances the absorption of the laser beam on the tissue surface, changing its chemical and morphological structure, and increasing its acid resistance (10,11,22,23). Previous studies revealed that diode laser increases fluoride uptake when enamel is irradiated in the presence of a fluoride compound, and they also stated that enamel must be irradiated in the presence of a pigmented coating substance to increase the acid resistance of enamel (10,11). According to this, the pigmented 5% NaF varnish used here acted as a photo-absorber for the diode laser photons, generating photothermal effects in enamel and changing the morphology of the enamel and, therefore, its roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that a combined fluoridelaser treatment makes enamel more resistant to acid than either laser treatment or fluoride treatment alone (1,3,(8)(9)(10)(11)(12)(13). The reason for that effect is that subablative low-energy laser irradiation and fluoride treatment may instantaneously transform enamel hydroxyapatite into fluoridated hydroxyapatite, reducing enamel solubility and preventing enamel demineralization (3).…”
Section: Introductionmentioning
confidence: 99%
“…-Formation of enamel white spot lesions Acid resistant varnish (Nail polish, Barielle, NY, USA) was painted all over the labial surface of the crowns except for a single window of 3 mm X 3 mm at the cervical 1/3 of the crown (9). After complete setting of the nail varnish all specimens were suspended in 20 ml of acidified buffered demineralizing solution for 48 h at 37 °C.…”
Section: -Selected Materialsmentioning
confidence: 99%
“…It is believed that various types of lasers under appropriate irradiation parameters can cause a number of structural and physicochemical changes that offer cariostatic features. Some of these changes involve purifying the enamel hydroxyapatite via decreasing carbonate and crystalline water, 27,28 reducing the enamel permeability via changing the enamel surface morphology to a melted and resolidified one, 29 increasing the fluoride deposition on enamel surfaces, 15 and inducing the formation of fluorapatite which is more resistant to acid demineralization than apatite with carbonate or hydroxyl ions. 30,31 There are hardly any studies on the effects of the diode laser on the dental structure, especially using enamel microhardness.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Some studies have investigated laser-fluoride combination treatment to verify whether the laser could enhance the effect of fluoride on the enamel structure and increase the resistance of the dental structure against acid demineralization. [14][15][16][17] Among various lasers, semiconductor diode lasers with several positive aspects, such as the small size, low cost, and ease of use in the oral cavity, have become quite popular in clinical practice. 18 However, few reports are found on the caries-preventive effect of diode lasers, with or without fluoride, on the dental enamel, particularly deciduous teeth.…”
Section: Introductionmentioning
confidence: 99%